DIFFERENT CATEGORIES OF ADVERBS IN LINGUISTICS - Nazarkosimova, Ozoda (Журнал иностранных языков и лингвистики, 2023)
Adverbs are highly complex and signiﬁcantly less studied than other major lexical categories such as nouns or verbs. The purpose of this article is to devote some much needed attention to this part of speech and to examine and compare adverbs of degree. For our research we took three adverbs hardly, barely, and scarcely. Though these adverbs are generally considered synonymous, they have a slight difference from each other and they are not interchangeable in every possible context. Each of the adverbs occurs with different words, in different registers and contexts, and forms different collocations. To determine the differences, we pay our attention mainly on the meaning and usage of each of the adverbs and on the words they occur with.